Gestational and Lactational Exposure to an Environmentally‐Relevant Mixture of Brominated Flame Retardants: Effects on Neurodevelopment and Metabolism. Issue 7 (24th March 2017) - Tung, Emily W. Y.; Kawata, Alice; Rigden, Marc; Bowers, Wayne J.; Caldwell, Don; Holloway, Alison C.; Robaire, Bernard; Hales, Barbara F.; Wade, Michael G.
Abstract : Background: Developmental exposure to brominated flame retardants (BFRs), including polybrominated diphenyl ethers (PBDEs) and hexabromocyclododecane (HBCDD), has been associated with impaired neurodevelopment and some symptoms of metabolic syndrome. However, there are inconsistencies in studies reporting neurodevelopmental effects with studies of pure substances more likely to report effects than studies of technical products. In addition, the influence of early BFR exposures on later development of metabolic disease‐like symptoms has not been investigated. This study examined the effects of perinatal exposure to an environmentally relevant mixture of BFRs based on relative levels observed in house dust, on several markers of neurodevelopment and metabolism in offspring. Methods: Sprague–Dawley female rats were fed a diet estimated to deliver daily doses of 0, 0.06, 20, or 60 mg/kg of a mixture of PBDEs and HBCDD from before mating to weaning. Offspring were weaned to control diet and subjected to neurobehavioral and metabolic assessments. Results: Exposure to BFRs decreased vertical movement in at postnatal day (PND) 32 and increased time to emerge to a lighted area on PND 105 in offspring of both sexes. Although early life exposure to the BFR mixture did not impact measures of glucose or insulin action, male offspring had significantly decreased fat pad weights at PND 46. Total cholesterol was increased in male and female offspring exposed to the highest dose at PND 21. Conclusions: These results suggest that gestational and lactational exposure to an environmentally relevant BFR mixture may induce changes in neurodevelopment and lipid metabolism in offspring. Birth Defects Research 109:497–512, 2017.© 2017 The Authors Birth Defects Research Published by Wiley Periodicals, Inc.